She Decides Reading Genesis 34 in Conversation with Narrative Ethics - Cifers, Carrie (2023)
Genesis 34 is a troubling tale that includes an ambiguous sexual encounter (possibly rape), deception, brutal violence against an unsuspecting city, and the silence—or silencing—of the only female character, Dinah. This article models wrestling with this difficult passage through linguistic analysis and a narrative ethics framework that monitors the functions of reticence in narrative. Attending to the two major informational gaps—the narrator’s evaluation and the perspective of Dinah—alerts readers to the centrality of the latter as the key to unlocking the former.